The Value of Auditor Assurance: Evidence from Loan Pricing - Blackwell, David W.; Noland, Thomas R.; Winters, Drew B. (Journal of Accounting Research, 1998)
This paper provides empirical evidence on the economic value of services provided by independent auditors by analyzing whether auditor association leads to reduced interest rates on revolving credit agreements. Using multivariate regressions, we analyze the relation between interest rates on revolving bank loans to small, private firms and the degree of auditor association with the financial statements provided to the lender,